A NEW SIGNING ALGORITHM BASED ON ELLIPTIC CURVE DISCRETE LOGARITHMS AND QUADRATIC RESIDUE PROBLEMS - Tahat, Nedal; Abdallah, Emad E. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper we propose a new digital signature algorithm for authenticity and integrity of a digital message. The core idea behind our approach is concentrated on using two hard problems in the signing process. The elliptic curve discrete logarithm and quadratic residue are engaged in a sophisticated manner to do the signing. The new proposed scheme provides higher level of security than other techniques that use a single hard problem. Clearly, Cybercriminals have to solve the two underlying hard problems simultaneously to destroy embedded signature. Extensive experimental results on several signed documents are performed to demonstrate the robustness of the proposed scheme against the most common attacks on digital signatures. Moreover, the computational complexity of the new scheme requires reasonable number of operations in both signing and verifying algorithms.